Advancing a health equity agenda across multiple policy domains: a qualitative policy analysis of social, trade and welfare policy. Issue 11 (6th November 2020) - Townsend, Belinda; Friel, Sharon; Freeman, Toby; Schram, Ashley; Strazdins, Lyndall; Labonte, Ronald; Mackean, Tamara; Baum, Fran
Abstract : Objective: While there is urgent need for policymaking that prioritises health equity, successful strategies for advancing such an agenda across multiple policy sectors are not well known. This study aims to address this gap by identifying successful strategies to advance a health equity agenda across multiple policy domains. Design: We conducted in-depth qualitative case studies in three important social determinants of health equity in Australia: employment and social policy (Paid Parental Leave); macroeconomics and trade policy (the Trans Pacific Partnership agreement); and welfare reform (the Northern Territory Emergency Response). The analysis triangulated multiple data sources included 71 semistructured interviews, document analysis and drew on political science theories related to interests, ideas and institutions. Results: Within and across case studies we observed three key strategies used by policy actors to advance a health equity agenda, with differing levels of success. The first was the use of multiple policy frames to appeal to a wide range of actors beyond health. The second was the formation of broad coalitions beyond the health sector, in particular networking with non-traditional policy allies. The third was the use of strategic forum shopping by policy actors to move the debate into more popular policy forums that were not health focused. Conclusions: This analysis provides nuanced strategies for agenda-setting for health equity and points to the need for multiple persuasive issue frames, coalitions with unusual bedfellows, and shopping around for supportive institutions outside the traditional health domain. Use of these nuanced strategies could generate greater ideational, actor and institutional support for prioritising health equity and thus could lead to improved health outcomes.